Investigation of flexible electrochemical sensor properties of graphite conductive ink modified textile products and their applications in electrical circuits - Dokur, Ebrar; Uruc, Selen; Kurteli, Rabianur; Gorduk, Ozge; Sahin, Yucel (ELSEVIER, 2023)
Smart textiles are of great interest due to their excellent applications in flexible and wearable devices. Therefore, in this study, conductive ink containing graphite was synthesized and conductive fabrics were obtained by coating the polyester/viscose blended fabric surface with the dip and dry method. Optimum conditions were determined by investigating the parameters that have an effect on the conductive fabric preparation such as dipping time, annealing temperature, time, and graphite amount. The resistivity value obtained from the optimum results is 0.075 & OHM;.cm. The characterization processes of the prepared conductive fabric were carried out by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray diffraction spectroscopy (XRD), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), and atomic force microscopy (AFM) methods. Then, the electrochemical sensor performance of the conductive fabric against dopamine, ascorbic acid, uric acid, and & beta;-nicotinamide adenine dinucleotide reduced form (NADH), which are essential for human health, and its application in electrical circuits was investigated. The results show that the e-textile prepared with graphite conductive ink has the potential to be used in the production of flexible and wearable sensors, which will be developed especially in the healthcare field.
Keywords: Conductive ink; Flexible electrode; Uric acid; Dopamine; NADH; COTTON FABRICS; GRAPHENE; ELECTRODES; NANOPARTICLES; NANOSHEETS; BEHAVIOR; POWDERS; Materials Science